Comparison of survival with somatostatin analog and chemotherapy and prognostic factors for treatment in 165 advanced neuroendocrine tumor patients with Ki-67 20% or less - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
The objectives of this study were to compare progression-free survival (PFS) with somatostatin analog (SSA) versus chemotherapy (CTx) in first-line therapy and to determine the patient group in which these treatments were more effective in neuroendocrine tumors (NETs) with a Ki-67 index of 20% or less. Patients who received SSA or CTx and had unresectable locally advanced and metastatic NETs with a Ki-67 index of 20% or less were retrospectively selected from 13 centers in the Turkish database between 2000 and 2015. One hundred and sixty-five patients were enrolled. The median age was 56 years and the male-to-female ratio was 1.09. Seventy-four (45%) patients were of grade 1 NET and 91 (55%) were of grade 2. SSA was given to 104 patients, whereas 61 were treated with CTx. The objective response rate after SSA was 15.4%; another 73.1% had stable disease. The objective response rate after CTx was 36.1%, and 40.9% had stable disease (P = 0.008). The median PFS in SSA patients was 21 months (95% confidence interval: 12.4-29.6), and 8 months for CTx (95% confidence interval: 5.5-10.6) (P < 0.001). There was no significant difference between PFS of receiving SSA and CTx in pancreatic neuroendocrine tumor (PNET) patients; however, the PFS of receiving SSA was longer in non-PNET patients (P < 0.001). SSA was better treatment in advanced NET patients with a Ki-67 index of less than 5%, having a primary resected and a performance status of 0 (P < 0.05). SSA may be preferred over CTx in advanced NET patients with low-to-intermediate grade. Copyright (C) 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: chemotherapy; Ki-67 index; lanreotide; neuroendocrine tumor; octreotide; pancreatic neuroendocrine tumor; somatostatin analog; CARCINOID-TUMORS; GRADING SYSTEM; OCTREOTIDE; LANREOTIDE; MIDGUT; INDEX